Lyudvik Vasili Mirzoyan - Babajanyan, Ṛ. A.; Hambaryan, V. V.; Hakobyan, A. A. (Li͡udvik Vasilʹevich Mirzoi͡an, 1998)
The biography and bibliography of the works of the Armenian Astro-Physicist Lyudvik Vasili Mirgoyan, b. 1923
At head of title: Hayastani Hanrapetutʻyan Gitutʻyunneri Azgayin Akademia, Fundamental Gitakan Gradaran.
The biography and bibliography of the works of the Armenian Astro-Physicist Lyudvik Vasili Mirgoyan, b. 1923
Armenian and Russian.
Keywords: Astrophysics / Bibliography.